2015
DOI: 10.2337/db15-0430
|View full text |Cite
|
Sign up to set email alerts
|

Elevations in Circulating Methylated and Unmethylated Preproinsulin DNA in New-Onset Type 1 Diabetes

Abstract: Elevated ratios of circulating unmethylated to methylated preproinsulin (INS) DNA have been suggested to reflect β-cell death in type 1 diabetes (T1D). We tested the hypothesis that absolute levels (rather than ratios) of unmethylated and methylated INS DNA differ between subjects with new-onset T1D and control subjects and assessed longitudinal changes in these parameters. We used droplet digital PCR to measure levels of unmethylated and methylated INS DNA in serum from subjects at T1D onset and at 8 weeks an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
105
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(119 citation statements)
references
References 16 publications
12
105
2
Order By: Relevance
“…Previously published cfDNA assays that detect β-cell death in T1D were limited by high background signal in healthy control subjects (21,22,24,25). We interpreted this signal as being caused by chance demethylation of CpGs in cfDNA from non-β-cell tissues.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previously published cfDNA assays that detect β-cell death in T1D were limited by high background signal in healthy control subjects (21,22,24,25). We interpreted this signal as being caused by chance demethylation of CpGs in cfDNA from non-β-cell tissues.…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies have identified unmethylated INS promoter DNA in the circulation of patients with recently diagnosed T1D and in islet-graft recipients, likely reflecting both autoimmune and alloimmune destruction of β cells (21)(22)(23)(24)(25). However, published data suggest that the analytic approaches used were not sufficiently specific to differentiate robustly between β-cell-and non-β-cellderived cfDNA.…”
Section: Significancementioning
confidence: 99%
“…4D). To assess β-cell apoptosis in vivo further, droplet digital PCR was used to measure circulating levels of unmethylated cell-free insulin 2 (Ins2) DNA in serum (41)(42)(43). Importantly, Atf5…”
Section: Atf5 Regulates the Susceptibility Of β Cells To Stress-inducedmentioning
confidence: 99%
“…ddPCR to verify mutation was done as described previously 21 . Samples were analyzed using a dual fluorescent probe-based multiplex assay.…”
Section: Methodsmentioning
confidence: 99%